Colorado's forest type map - Colorado State Forest Service, cartographer (Colorado State University. Libraries, 2007)
Map highlighting various types of forests in Colorado.
Keywords: Colorado -- Maps; lodgepole pine; aspen; mixed conifer; montane riparian; ponderosa pine; oak shrubland; pinyon-juniper; spruce-fir; plains riparian